Enhancing Physics Learning with Advance Organizer: A Meta-Cognitive Approach - Anandita, Aulia Silvina; Adi, Nugroho Prasetya; Baihaqi, Habibah Khusna (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2025)
Physics education often presents challenges for students due to its abstract and complex nature. Many students struggle to comprehend the interrelationships between concepts and tend to memorize formulas without developing a deep conceptual understanding. This study aims to evaluate the effectiveness of the Advance Organizer as a metacognitive approach to enhance students' scientific literacy, conceptual understanding, and mathematical communication skills. The research method employed is Research and Development (R&D) using the 4D model (Define, Design, Develop, and Disseminate), combined with a quasi-experimental design employing the Nonequivalent Control Group Design. The developed instructional materials include lesson plans (RPP), student worksheets (LKPD), interactive visual-based learning media, and assessment instruments. The findings indicate that students in the experimental group using the Advance Organizer demonstrated significantly greater improvements in conceptual understanding compared to the control group. The average scientific literacy score increased from 71.88 to 83.22 (N-Gain = 0.40, moderate category), while mathematical communication skills improved from 68.03 to 79.38 (N-Gain = 0.35, moderate category). Statistical analysis using Hotelling’s T² test revealed a significant difference between the experimental and control groups (F = 14.755, p < 0.05), while effect size analysis using Cohen’s f showed a large impact on scientific literacy (f = 0.625) and a moderate impact on mathematical communication (f = 0.342). Although this strategy proved effective, several challenges were identified, including students' initial difficulties in adapting to active learning methods and the need for teacher training in designing optimal Advance Organizers. This study recommends integrating the Advance Organizer with digital technology and further exploring its application across various physics topics to enhance the effectiveness of metacognitive-based learning.